Expanding Research on Firefighter Trainee Fitness, Reasons for Academy Release, and the Predictive Capabilities of Fitness Tests. - Lockie, Robert G.; Orr, Robin M.; Montes, Fernando; Dawes, J. Jay (Journal of Strength & Conditioning Research, 2024)
Firefighter trainees need a level of fitness to be admitted to and complete a training academy. Fitness could indicate a trainee's likelihood of graduation, in addition to their reasons for release. This study determined fitness differences between firefighter trainees who graduated (GRAD) from academy or were released because of injury (RELI), performance test failures (RELP), or resignation (RELR), and whether fitness predicted graduation. Occupational physical ability test (OPAT) data for 686 trainees were analyzed, including: Illinois agility test; push-ups; pull-ups; leg tucks; maximal aerobic capacity (...O2max); backward overhead medicine ball throw; 10-repetition maximum deadlift; and farmer's carry. Raw and scaled (based on internal scoring) scores were recorded. Trainees were split into GRAD (n = 576), RELI (n 5 33), RELP (n = 66), and RELR (n = 11) groups. A 1-way ANOVA with Bonferroni post hoc calculated between-group differences. Stepwise linear regression determined whether fitness predicted group inclusion. Receiver operating curves and area under the curve (AUC) derived test accuracy for predicting academy release. The GRAD group was superior (p ≤ 0.04) to the RELI group in all tests except push-ups, pull-ups, and farmer's carry; RELP group in all tests except the farmer's carry; and RELR group in ...O2max, deadlift, and total OPAT score. Select fitness tests could predict inclusion in each group, although the explained variances were low (~1 -11%). Raw ...O2max (AUC = 0.71) and total OPAT score (AUC = 0.74) had acceptable prediction accuracy. Fitness influenced academy graduation and reasons for release. Scaled scores could predict group inclusion in this department; ...O2max and total OPAT score provided the most accurate predictors for release.